Peran Lingkungan Komunikasi Keluarga Dalam Penanganan Anak Speech Delay: Studi Kasus Di Desa Sumberejo Madiun - Siti Nurhaliza (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the role of the family communication environment in dealing with children with speech delay in Sumberejo Village, Madiun. Using a qualitative case study method, data were obtained through in-depth interviews and observations of seven parents. The results of the study show that active, passive, or inconsistent family communication patterns have a direct effect on children's speech development. Education increased parents' understanding from 28.6% to 85.7%, which was followed by changes in communication behavior and progress in children's speech abilities. This study emphasizes the importance of family communication as an effective intervention in a rural context.